O33 Towards personalised weaning of sedatives and analgesics using mechanism-based modelling of iatrogenic withdrawal in critically ill children. Issue 6 (17th May 2019) - Goulooze, S; Krekels, E; van Dijk, M; Hankemeier, T; Tibboel, D; Ista, E; Knibbe, C
Abstract : Background: Prolonged treatment with analgesics and sedatives can result in iatrogenic withdrawal syndrome (IWS) in children being weaned from these drugs. 1 Personalized weaning strategies might lower the incidence of IWS, but this requires a quantitative understanding of withdrawal over time in individual patients. Methods: Data from 81 children (aged 1 month to 17 years) collected during an observational clinical study on IWS 2 were used, including a total of 1782 withdrawal assessments performed by PICU nurses, on a numerical rating scale (NRSwithdrawal ) from 0 (no withdrawal) to 10 (worst withdrawal possible). Population pharmacokinetic models from literature were used to generate concentration-time profiles in each patient of all key analgesics and sedatives: morphine, fentanyl, methadone, midazolam, lorazepam, propofol, esketamine and clonidine. A mechanism-based withdrawal model was developed using NONMEM 7.3 to quantify IWS over time. The final model was used to perform simulations in which different weaning strategies were compared. Results: A novel mechanism-based withdrawal model structure was developed with a hypothetical compartment, which equilibrates with the central pharmacokinetic compartment, and which characterizes the development and disappearance of drug dependence over time. With this model and available data, withdrawal dynamics could be established with statistical significance for fentanyl (p< 10 -6 ), morphine (p=0.043) and esketamine (p=0.002), and not for any of the other drugs. Compared with fentanyl, development and disappearance of esketamine and morphine dependence is slower. Conclusions: Given the patient's use of fentanyl, morphine and esketamine, the developed model can dynamically predict IWS from these substances under different weaning strategies. The results show that the optimal strategy for weaning of drug dependent children depends on both the type of drug and the drug levels prior to weaning. In this study, there was insufficient information to characterise midazolam withdrawal dynamics, potentially because of slow midazolam weaning with insufficiently high NRSwithdrawal scores. References: Best KM, Boullata JI, Curley MAQ. Risk factors associated with iatrogenic opioid and benzodiazepine withdrawal in critically ill pediatric patients: A Systematic Review and Conceptual Model. Pediatr Crit Care Med ( 2015) 16(2): 175–183. Ista E, de Hoog M, Tibboel D, Duivenvoorden HJ, van Dijk M. Psychometric evaluation of the sophia observation withdrawal symptoms scale in critically ill children. Pediatr Crit Care Med ( 2013).14(8): 761–769. Disclosure(s): Nothing to disclose